Epigenetic Therapy of Non-Small Cell Lung Cancer Using Decitabine (5-Aza-2′-Deoxycytidine) - Momparler, Richard L. (Frontiers in Oncology, 2013)
Epigenetic analysis shows that many genes that suppress malignancy are silenced by aberrant DNA methylation in lung cancer. Many of these genes are interesting targets for reactivation by the inhibitor of DNA methylation, decitabine (5-aza-2’-deoxycytidine, DAC). A pilot study on intense dose DAC showed promising results in patients with metastatic non-small cell lung cancer (NSCLC). However, subsequent clinical studies using low dose DAC were not very effective against NSCLC and interest in this therapy diminished. Recently, interesting responses were observed in a patient with NSCLC following treatment with a combination of the related inhibitor of DNA methylation, 5-azacytidine and an inhibitor of histone deacetylation. This finding has generated a renewed interest in the epigenetic therapy of lung cancer. Preclinical studies indicate that DAC has remarkable chemotherapeutic potential for tumor therapy. This epigenetic agent has a delayed and prolonged epigenetic action on tumor cells. This delayed action should be taken into consideration in the design and evaluation of clinical studies on DAC. Future research should be directed at finding the optimal dose-schedule of de DAC for the treatment of NSCLC.